Tri-modal mesoporous carbon/sulfur nanocomposite for high performance Li-S battery. (1st February 2016) - Hu, Wen; Zhang, Huamin; Wang, Meiri; Zhang, Hongzhang; Qu, Chao
Abstract: A novel tri-modal mesoporous carbon (TMC)/S composite as a high performance cathode for Li-S battery is reported. The TMC host, synthesized by a simple sol-gel templating method, possesses one of the highest surface area of 2371 m 2  g −1, pore volume of 2.85 cc g −1 and a unique tri-modal mesopore structure (2.5 nm/9 nm/15 nm). Electrochemical tests reveal that the TMC/S–50 wt% nanocomposite cathode delivers an initial capacity up to 1029 mAh g −1 at 3350 mA g −1 (2C), and maintains a high reversible capacity of 843 mAh g −1 after 100 cycles. And it retains a stable capacity of 708 mAh g −1 after 100 cycles at 5025 mA g −1 (charge/discharge in 20 min, 3C). Even with a higher sulfur loading, the TMC/S–70 wt% nanocomposite still reaches a reversible capacity of 700 mAh g −1, and demonstrates a very low decay rate of only 0.088% per cycle over 300 cycles at 838 mA g −1 (0.5C). We attribute such superior performance to the collective effect of tri-modal mesopore architecture, especially to the contribution of the exterior large mesopores (15 nm), designed being not only large enough to accommodate rapid electrolyte transport, moreover, small enough to serve as additional buffer spaces for polysulfides entrapment.